Midyat Kentinde Yer Alan Yiyecek-İçecek İşletmelerine Yönelik Tripadvisor Paylaşımlarının İncelenmesi. - Şeyhanlıoğlu, Hasan Önal; İleri, Saadet (Electronic Turkish Studies)
This research examines online consumer complaints about restaurant businesses operating in the district of Midyat, which stands out for its rich cultural heritage and multicultural structure, within the context of electronic word-of-mouth communication (e-WOM). In recent years, digital platforms have played an increasingly decisive role in tourist destination preferences; user reviews have become an important source of data both in evaluating the service quality of businesses and in shaping the image of destinations. Accordingly, the study systematically evaluated a total of 359 user reviews shared on TripAdvisor about 17 restaurants in Midyat using content analysis methods. Analysis of negative reviews categorised as ‘terrible,’ ‘poor,’ and ‘average’ revealed that complaints fell under five main themes: (i) service environment, (ii) staff attitude and behaviour, (iii) service process, (iv) menu variety and adequacy, and (v) pricing policy. The findings show that elements related to the service environment, such as hygiene, noise, and spatial layout, have a critical impact on tourist satisfaction; staff behaviour and service disruptions can directly weaken the destination's image. The study highlights the decisive role of digital customer experiences in the development of gastronomic tourism. However, the insufficient representation of local flavours on the menu and the mismatch between price and performance are other problem areas frequently emphasised in e-WOM content. The study reveals that, in terms of the sustainability of gastronomic tourism in Midyat, the regular monitoring of digital customer experiences, transparent pricing policies, staff training, and improvements to the service environment are of strategic importance. Ultimately, the research contributes both theoretically and practically to the literature on the effects of e-WOM on regional destination perception, service quality management, and customer satisfaction.